2021
DOI: 10.1158/2159-8290.cd-20-0263
|View full text |Cite
|
Sign up to set email alerts
|

Lower Airway Dysbiosis Affects Lung Cancer Progression

Abstract: In lung cancer, enrichment of the lower airway microbiota with oral commensals commonly occurs and ex vivo models support that some of these bacteria can trigger host transcriptomic signatures associated with carcinogenesis. Here, we show that this lower airway dysbiotic signature was more prevalent in group IIIB-IV TNM stage lung cancer and is associated with poor prognosis, as shown by decreased survival among subjects with early stage disease (I-IIIA) and worse tumor progression as measured by RECIST scores… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
182
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 192 publications
(195 citation statements)
references
References 92 publications
2
182
0
Order By: Relevance
“…Interestingly, the bacterial signatures also identi ed Mycoplasma salivarium, a known oral commensal that has previously been associated with ventilator-acquired pneumonia 63 , as differentially active in those who died and those who were ventilated for more than 28 days when compared to those ventilated less than 28 days. From previous data published by us, enrichment of the lower airway microbiota with oral commensals was seen to be associated with a pro-in ammatory state in several diseases including lung cancer 64,65 and nontuberculosis mycobacterium related bronchiectasis 66 .…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, the bacterial signatures also identi ed Mycoplasma salivarium, a known oral commensal that has previously been associated with ventilator-acquired pneumonia 63 , as differentially active in those who died and those who were ventilated for more than 28 days when compared to those ventilated less than 28 days. From previous data published by us, enrichment of the lower airway microbiota with oral commensals was seen to be associated with a pro-in ammatory state in several diseases including lung cancer 64,65 and nontuberculosis mycobacterium related bronchiectasis 66 .…”
Section: Discussionmentioning
confidence: 82%
“…Interestingly, the bacterial signatures also identified Mycoplasma salivarium , a known oral commensal that has previously been associated with ventilator-acquired pneumonia 61 , as differentially active in those who died and those who were ventilated for more than 28 days when compared to those ventilated less than 28 days. From previous data published by us, enrichment of the lower airway microbiota with oral commensals was seen to be associated with a pro-inflammatory state in several diseases including lung cancer 62,63 and non-tuberculosis mycobacterium related bronchiectasis 64 .…”
Section: Discussionmentioning
confidence: 82%
“…Tsay et al showed that Veillonella parvula was the most abundant taxon driving this dysbiotic association, leading to upregulation of the IL17, PI3K, MAPK, and ERK pathways in the airway transcriptome. They then used V. parvula in the murine KP lung cancer model, characterizing the mechanistic effects on lower airway CD4+ and CD8+, neutrophils, and Th17 recruitment (59). Also, Peters et al recently demonstrated through 16s rRNA gene sequencing of lung samples from NSCLC patients that lung tumor tissue was correlated with significantly lower bacterial richness and diversity, and that alterations in the relative abundance of families such as Koribacteraceae, Bacteroidaceae, Lachnospiraceae, and Ruminococcaceae were associated with increased or decreased recurrence-free and disease-free survival (60).…”
Section: Does the Gut Microbiota Play A Role In Lung Cancer?mentioning
confidence: 99%
“…showed that Veillonella parvula was the most abundant taxon driving this dysbiotic association, leading to upregulation of the IL17, PI3K, MAPK, and ERK pathways in the airway transcriptome. They then used V. parvula in the murine KP lung cancer model, characterizing the mechanistic effects on lower airway CD4+ and CD8+, neutrophils, and Th17 recruitment ( 59 ). Also, Peters et al.…”
Section: Does the Gut Microbiota Play A Role In Lung Cancer?mentioning
confidence: 99%